Properties of Chemically Modified (Selected Silanes) Lignocellulosic Filler and Its Application in Natural Rubber Biocomposites - Miedzianowska, Justyna (Materials (Basel), 2020)
This article concerns the functional properties of elastomeric composites reinforced with modified lignocellulosic material obtained from cereal straw. The aim of the research was to acquire new knowledge on the effectiveness of cereal straw modification methods in multifunctional properties, while reducing the flammability of newly designed elastomeric materials made of natural rubber. The article deals with investigating and explaining dependencies that affect the performance and processing properties of polymer biocomposites containing modified cereal straw. Three different silanes were used to modify the lignocellulosic filler: n-Propyltriethoxysilane, Vinyltriethoxysilane, and 3,3′-Tetrathiobis(propyl-triethoxysilane). The influence of the conducted modifications on the morphology and structure of straw particles was investigated using a scanning electron microscope, contact angle measurements, and thermogravimetric analysis technique. The increase in hydrophobicity and thermal stability of natural fibers was confirmed. In turn, the impact of silanization on the properties of filled composites was determined on the basis of rheometric characteristics and cross-linking density, static mechanical properties, tear resistance, thermal stability, and flammability tests. Noteworthy was the improvement of the mechanical strength of biocomposites and their resistance to burning. Correlations affecting the structure, morphology, dispersion, and properties of produced composites can facilitate the indication of a further research path in the field of development of new elastomeric biomaterials.